2017
DOI: 10.1371/journal.pone.0181358
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance rates in gram-positive bacteria do not drive glycopeptides use

Abstract: Surveillance data are considered essential to appropriate empiric antibiotic therapy and stewardship. The objective of this study was to determine if a change in the rates of antibiotic resistance impacts antibiotic use in European hospitals. Glycopeptides use was selected to study the correlation between resistance rates and antibiotic use because of the restricted spectrum against resistant gram positive bacteria. PubMed, ECDC databases and national/regional surveillance systems were searched to identify gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[19] showed in a meta-analysis a positive correlation between the rate of MRSA and the glycopeptide usage. However, this was not corroborated in an eight-country study, with more than 5% decrease of MRSA infection, which found only a negative correlation between glycopeptide use and MRSA rates [22]. Moreover, Mascitti et al .…”
Section: Discussionmentioning
confidence: 91%
“…[19] showed in a meta-analysis a positive correlation between the rate of MRSA and the glycopeptide usage. However, this was not corroborated in an eight-country study, with more than 5% decrease of MRSA infection, which found only a negative correlation between glycopeptide use and MRSA rates [22]. Moreover, Mascitti et al .…”
Section: Discussionmentioning
confidence: 91%
“…Even when data are available, it seems that the prescribers do not trust it. For example, an epidemiological study correlated resistance rates of Gram-positive bacteria and glycopeptide antibiotic use in 31 countries over a period of 19 years [58]. In the majority of countries, use of glycopeptides increased and the rates of MRSA bloodstream infections decreased, while bloodstream infections with meticillinresistant coagulase negative staphylococci and vancomycinresistant enterococci were unchanged.…”
Section: Linking Surveillance and Stewardship Interventionmentioning
confidence: 99%
“…Gram positive pathogens are still a major problem in human health, particularly drug resistant strains (27), emphasising the need for the discovery of novel biological agents targeting this group of bacteria. This study focuses on a strain of Streptococcus gallolyticus, a species originally described as Streptococcus bovis.…”
Section: Introductionmentioning
confidence: 99%